2019
DOI: 10.3390/jcm8030401
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Female Child Sexual Offenders—Needs and Challenges for Practice and Research

Abstract: This article provides a short literature overview on female child sexual offenders (FCSO) focusing on the discrepancy between prevalence rates from different sources, characteristics of FCSO and their victims, as well as the societal “culture of denial” surrounding these women. FCSO are a powerful social taboo. Even professionals in the healthcare or justice system were shown to respond inappropriately in cases of child sexual abuse committed by women. As a result, offences of FCSO may be underreported and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 67 publications
1
31
0
2
Order By: Relevance
“…Because of methodological weaknesses in most FSO research, experts question the accuracy of this scholarship since these studies often use small or nonrepresentative convenience samples. Thereby, making it impossible for researchers to generalize and infer from the findings (Saradjian, 2000;Tozdan et al, 2019). This is only one factor that prevents experts and scholars from assessing the total number of incidents and cases that occur each year.…”
Section: Prevalence and Typologies Of Fsosmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of methodological weaknesses in most FSO research, experts question the accuracy of this scholarship since these studies often use small or nonrepresentative convenience samples. Thereby, making it impossible for researchers to generalize and infer from the findings (Saradjian, 2000;Tozdan et al, 2019). This is only one factor that prevents experts and scholars from assessing the total number of incidents and cases that occur each year.…”
Section: Prevalence and Typologies Of Fsosmentioning
confidence: 99%
“…Despite these concerns, efforts are made to assess the actual number of female sexual offenses that occur. For example, Tozdan, Briken, & Dekker (2019) reported that in the U.S., official crime data from the National Incident Based Reporting System (NIBRS), that focused on female sexual offenses committed by relatives of the victims, revealed from 1991-1996, women offenders committed an estimated 40,804 sexual crimes against children and adolescents between the ages 1 through 17. More specifically, NIBRS data revealed that 8,539 victims were younger than 6; 12,260 victims were ages 6-12; and 20,005 victims were between the ages of 12-17.…”
Section: Efforts To Assess the Pervasiveness Of Fsomentioning
confidence: 99%
See 1 more Smart Citation
“…In keinem der vorliegenden Dokumente wurde eine Täterschaft ausschließlich von Frauen angegeben; eher waren sowohl Männer als auch Frauen oder ausschließlich Männer involviert. Von Frauen begangener sexueller Kindesmissbrauch stellt ein gesellschaftliches Tabuthema dar [16,17], was insbesondere im Gesundheitswesen und in der Justiz deutlich wird [18,19]. Betroffene von Täterinnen haben oft Schwierigkeiten, sexuell missbräuchliche Handlungen als solche einzuordnen [16] oder darüber zu sprechen.…”
Section: Diskussionunclassified
“…This phenomenon has been researched in relation to perceptions of working parents (Cuddy et al, 2004;Fuegen & Endicott, 2010;Gaunt, 2013;Rudman & Mescher, 2013), job applications (Phelan et al, 2008;Rudman & Glick, 1999), leadership abilities and skills (Eagly & Karau, 2002), judicial decision-making (Pozzulo et al, 2009;Miller, 2018), or feminine-and masculinelooking robots (Eyssel & Hegel, 2012), among others. It has also been demonstrated in the context of immoral behaviors, such as sexual assault (Davies & Rogers, 2006;Fromuth et al, 2001;Gakhal & Brown, 2011), child sexual abuse (Tozdan et al, 2019;Zack et al, 2018), intimate partner violence (Cormier & Woodworth, 2008;Dutton & White, 2013;Hamby & Jackson, 2010;Jackson Harris & Cook, 1994;Seelau & Seelau, 2003;Seelau & Seelau, 2005), and-as described above-sexual harassment (Bursik & Gefter, 2011;Pina & Gannon, 2010;Studzinska & Hilton, 2017). Frequently, for opposite-gender cases, female victims were viewed as suffering more than male victims, and male perpetrators were regarded as deserving more punishment or being more responsible than female perpetrators.…”
Section: Theory Development and Hypothesesmentioning
confidence: 99%